Different Design Feature Combinations of Flatfoot Orthosis on Plantar Fascia Strain and Plantar Pressure: A Muscle-Driven Finite Element Analysis With Taguchi Method - Peng, Yinghu; Wang, Yan; Wong, Duo Wai-Chi; Chen, Tony Lin-Wei; Chen, Shane Fei; Zhang, Guoxin; Tan, Qitao; Zhang, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
Customized foot orthosis is commonly used to modify foot posture and relieve foot pain for adult acquired flexible flatfoot. However, systematic investigation of the influence of foot orthotic design parameter combination on the internal foot mechanics remains scarce. This study aimed to investigate the biomechanical effects of different combinations of foot orthoses design features through a muscle-driven finite element flatfoot model. A flatfoot-orthosis finite element model was constructed considering the three-dimensional geometry of plantar fascia. The plantar fascia model accounted for the interaction with the bulk soft tissue. The Taguchi approach was adopted to analyze the significance of four design factors combination (arch support height, medial posting inclination, heel cup height, and material stiffness). Predicted plantar pressure and plantar fascia strains in different design combinations at the midstance instant were reported. The results indicated that the foot orthosis with higher arch support (45.7 %) and medial inclination angle (25.5 %) effectively reduced peak plantar pressure. For the proximal plantar fascia strain, arch support (41.8 %) and material stiffness (37 %) were strong influencing factors. Specifically, higher arch support and softer material decreased the peak plantar fascia strain. The plantar pressure and plantar fascia loading were sensitive to the arch support feature. The proposed statistics-based finite element flatfoot model could assist the insole optimization and evaluation for individuals with flatfoot.